2012
DOI: 10.1586/era.11.175
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea: a key player in cancer chemotherapy

Abstract: Hydroxyurea (HU) is a simple organic compound currently used as a cancer chemotherapeutic agent. It acts specifically on the S-phase of the cell cycle by inhibiting the enzyme ribonucleoside diphosphate reductase, thereby hindering the reductive conversion of ribonucleotides to deoxyribonucleotides and thus limiting de novo DNA synthesis. HU is employed in hemotological settings as a first-line treatment of myeloproliferative disorders, such as polycythemia vera, essential thrombocythemia and primary myelofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 63 publications
2
83
0
Order By: Relevance
“…In this review, we summarize the main cellular responses to dNTP depletion caused by treatment with hydroxyurea (HU), a reversible inhibitor of the ribonucleotide reductase (RNR) [7]. This agent is widely used in fundamental research and as chemotherapeutic agent [8]. Mechanistically, HU quenches the tyrosyl free radical at the active site of the RNR component M2, inactivating the RNR enzyme [9, 10].…”
Section: Sources Of Dna Replication Fork Pausing Slow-down and Arrestmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we summarize the main cellular responses to dNTP depletion caused by treatment with hydroxyurea (HU), a reversible inhibitor of the ribonucleotide reductase (RNR) [7]. This agent is widely used in fundamental research and as chemotherapeutic agent [8]. Mechanistically, HU quenches the tyrosyl free radical at the active site of the RNR component M2, inactivating the RNR enzyme [9, 10].…”
Section: Sources Of Dna Replication Fork Pausing Slow-down and Arrestmentioning
confidence: 99%
“…The practical importance of studying the cellular responses to DNA replication fork arrest lies in the fact that many DNA replication inhibitors, such as HU, are chemotherapeutic agents [8]. Therefore, the knowledge of the underlying molecular mechanisms and responses can inform therapeutic approaches.…”
Section: Sources Of Dna Replication Fork Pausing Slow-down and Arrestmentioning
confidence: 99%
“…As tumor cells have a higher need for dNTPs [55, 56], many of the anti-tumor therapeutics affecting nucleotide metabolism are aimed at RNR [8387]. The first class of drugs that were found to inhibit nucleotide metabolism are free radical scavengers, including hydroxyurea [88] and trimidox (Figure 2) [89]. Because these compounds are free radical scavengers, they can inhibit RNR by inactivating the tyrosyl radical on R2 necessary for its reductive capacity [89–94].…”
Section: Nucleotide Metabolism In Cancermentioning
confidence: 99%
“…In contrast, hydroxyurea (HU), a well-established antineoplastic drug, 63 was predicted by our method to be a potential carcinogen. A previous study showed that a specific dosage of HU may enhance skin carcinogenesis, 64 but no further study has indicated HU as a carcinogen.…”
Section: Carcinogenic and Non-carcinogenic Candidates With Low Structmentioning
confidence: 98%